2019
DOI: 10.3390/met9070764
|View full text |Cite
|
Sign up to set email alerts
|

Deposits in Gas-fired Rotary Kiln for Limonite Magnetization-Reduction Roasting: Characteristics and Formation Mechanism

Abstract: The formation mechanism of deposits in commercial gas-fired magnetization-reduction roasting rotary kiln was studied. The deposits ring adhered on the kiln wall based on the bonding of low melting point eutectic liquid phase, and the deposit adhered on the air duct head by impact deposition. The chemical composition and microstructure of the deposits sampled at different locations varied slightly. Besides a small amount of quartz and limonite, main phases in the deposits are fayalite, glass phase and magnetite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, because of the pressure exerted by the rolling pellet layer, the volume of the primary deposit is continuously compressed and eventually forms a tight structure. The newly formed deposits continue to grow on the primary deposits, thickening layer by layer, further impeding the advance of the rolling pellets layer [30]. [27].…”
Section: The Agglomerating Mechanism Of Depositmentioning
confidence: 99%
“…Furthermore, because of the pressure exerted by the rolling pellet layer, the volume of the primary deposit is continuously compressed and eventually forms a tight structure. The newly formed deposits continue to grow on the primary deposits, thickening layer by layer, further impeding the advance of the rolling pellets layer [30]. [27].…”
Section: The Agglomerating Mechanism Of Depositmentioning
confidence: 99%
“…In the rotary kilns fueled by pulverized coal, preheated iron ore pellet powder and coal ash are the material basis for deposit formation. The characterization of the deposits showed that the main mineralogical phases include hematite, silicate, and some minor glass phases. Some studies have found differences in the mechanism of deposit formation in different parts of the rotary kiln. , The primary manner to form the deposits near the burner zone in the rotary kiln was the hematite crystallization and diffusion, while the liquid phases played a secondary role in the deposit formation. Furthermore, bentonite and coal ash contain high SiO 2 , Al 2 O 3 , Na 2 O, and K 2 O, which will promote the generation of liquid phases and intensify the deposition phenomenon. ,, In addition, insufficient combustion of pulverized coal caused partial zones of the reduction atmosphere in the rotary kiln, resulting in the generation of Fe 2+ , and formed low-melting-temperature compounds with veinstone minerals such as SiO 2 and CaO Al 2 O 3 . It has been found that the deposition phenomenon became more severe in rotary kilns for producing fluxed iron ore pellets. , Unfortunately, the effects of the basicity of iron ore pellets on the deposition formation mechanism are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%